(n-5)(8n-7)=0

Simple and best practice solution for (n-5)(8n-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n-5)(8n-7)=0 equation:


Simplifying
(n + -5)(8n + -7) = 0

Reorder the terms:
(-5 + n)(8n + -7) = 0

Reorder the terms:
(-5 + n)(-7 + 8n) = 0

Multiply (-5 + n) * (-7 + 8n)
(-5(-7 + 8n) + n(-7 + 8n)) = 0
((-7 * -5 + 8n * -5) + n(-7 + 8n)) = 0
((35 + -40n) + n(-7 + 8n)) = 0
(35 + -40n + (-7 * n + 8n * n)) = 0
(35 + -40n + (-7n + 8n2)) = 0

Combine like terms: -40n + -7n = -47n
(35 + -47n + 8n2) = 0

Solving
35 + -47n + 8n2 = 0

Solving for variable 'n'.

Factor a trinomial.
(7 + -8n)(5 + -1n) = 0

Subproblem 1

Set the factor '(7 + -8n)' equal to zero and attempt to solve: Simplifying 7 + -8n = 0 Solving 7 + -8n = 0 Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -8n = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -8n = 0 + -7 -8n = 0 + -7 Combine like terms: 0 + -7 = -7 -8n = -7 Divide each side by '-8'. n = 0.875 Simplifying n = 0.875

Subproblem 2

Set the factor '(5 + -1n)' equal to zero and attempt to solve: Simplifying 5 + -1n = 0 Solving 5 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1n = 0 + -5 -1n = 0 + -5 Combine like terms: 0 + -5 = -5 -1n = -5 Divide each side by '-1'. n = 5 Simplifying n = 5

Solution

n = {0.875, 5}

See similar equations:

| x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 | | 60=12+6(n-1) | | 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 | | -17-5p=5(2+4p)+2p | | -58.75-x/8=7x/8+191.25 | | 14b-13b+3b=20 | | u(6u-7)=0 | | 4ln(7x)=16 | | -17-5p=5(2+4)+2p | | 3x^3-2x^2-12x+18=0 | | 6w+5w-9w=12 | | 5y(y+2)=0 | | 2tanx+7=3 | | 6+2x-5=6-3(2x-1) | | 10h-8h+h-3h+h=7 | | 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p | | 20-2=38 | | -3(x-4)+2xy=xy-5x+xy-6 | | 2w^2-22w+48=0 | | 5(2)-2=38 | | (3g+2)(9g+5)=0 |

Equations solver categories